Spatial distribution and factors influencing modern contraceptive practice among tribal married women in India: evidence from National Family Health Survey 5 (2019-2021) - Sushree Nibedita Panda; Manish Barik; Ardhendu Sekhar Acharya; Srikanta Kanungo; Sanghamitra Pati (BMC, 2023)
Abstract Background The unmet need for family planning has been a public health concern in developing countries, especially in the south-east region. In India, the expanding roles of women has led to a growing need for family planning and contraception. However, tribal women still struggle with reproductive and sexual health issues. Unfortunately, most tribal women are not informed about the potential health risks associated with contraceptive use, as service providers often neglect to provide this information. As a result, tribal women often suffer in silence, which can lead to serious health problems. Thus, the present study aimed to understand the patterns and factors associated with modern contraceptive usage as well as the district level variation in usage among tribal married women. Methods We included 91,976 tribal married women participants aged 15 to 49 years from National Family Health Survey 5 conducted during the years 2019 to 2021. Descriptive statistics were used to compute the prevalence of modern contraceptive usage along with 95% confidence interval (CI) as a measure of uncertainty. The association between various socio-demographic predictors and modern contraceptive usage were assessed by multivariable logistic regression and presented as an adjusted odds ratio (AOR). Results The overall prevalence of modern contraceptive practices was found to be 53% among tribal married women, which was below the national average. Sterilization was the most preferred method of modern contraceptive, whereas injectables were the least preferred method. More than 80% of the married women get the family planning information from the public health facility and health workers. Districts of eastern and north-eastern states have comparatively less modern contraceptive prevalence than central and southern states. Age, education, parity and access to media were significantly associated with the use of modern methods of contraception. Conclusion Improving contraceptive use and reducing unmet needs for contraception among tribal women requires sustained efforts from healthcare workers, including Information Education and Communication (IEC) through mass media to raise awareness. A tailored family planning strategy is crucial to address the specific needs of tribal women at both the local and national levels, with adequate resources and monitoring for impact with this India can achieve Total Fertility Rate (TFR) 2.1 among tribals.